Disiplin Rohani sebagai Faktor Penentu Pertumbuhan Iman dan Keterlibatan Pelayanan Jemaat di GPdI Rhema Tarakan - Mangetek, Adriano; Arifianto, Yonatan Alex; Triposa, Reni (STT INDONESIA MANADO, 2025)
Abstract: The background of this study stems from the phenomenon of declining spiritual discipline among congregations, where many Christians are active in ministry but lack diligence in prayer, Bible reading, and fellowship, resulting in suboptimal growth in faith. This condition is also evident in GPdI Rhema Tarakan, where some congregants are not consistent in practising spiritual discipline, which is the main foundation for maturity in faith and Christ-like character. This study aims to analyse the influence of spiritual discipline on the growth of faith among the congregation of GPdI Rhema Tarakan and to identify the most dominant aspects of spiritual discipline in supporting their growth in faith. The research method used is descriptive qualitative, with a field study approach through interviews, observation, and documentation, as well as reinforcement from relevant literature reviews to obtain a deep and contextual understanding of the relationship between spiritual discipline and the growth of the congregation's faith. The results of the study show that spiritual discipline has a strong theological foundation and is the main means for the formation of mature faith in the life of the congregation. Consistent practices of spiritual discipline, such as prayer, reading the Word, and fellowship, have been proven to have a direct influence on the congregation's involvement in ministry and to foster the character of Christ in their daily lives. Thus, spiritual discipline not only strengthens individual faith growth, but also has significant implications for the holistic progress and growth of the local church. Abstrak: Latar belakang penelitian ini berangkat dari fenomena menurunnya disiplin rohani di kalangan jemaat, di mana banyak orang Kristen aktif dalam pelayanan namun kurang tekun dalam doa, pembacaan Alkitab, dan persekutuan, sehingga pertumbuhan iman tidak berkembang secara optimal. Kondisi ini juga terlihat di GPdI Rhema Tarakan, di mana sebagian jemaat belum konsisten menjalankan disiplin rohani yang menjadi fondasi utama bagi kedewasaan iman dan karakter Kristus. Penelitian ini bertujuan untuk menganalisis disiplin rohani terhadap pertumbuhan iman jemaat GPdI Rhema Tarakan serta mengidentifikasi aspek disiplin rohani yang paling dominan dalam mendukung pertumbuhan iman mereka. Metode penelitian yang digunakan adalah kualitatif deskriptif, dengan pendekatan studi lapangan melalui wawancara, observasi, dan dokumentasi, serta penguatan dari kajian pustaka yang relevan untuk memperoleh pemahaman yang mendalam dan kontekstual mengenai hubungan antara disiplin rohani dan pertumbuhan iman jemaat. Hasil penelitian menunjukkan bahwa disiplin rohani memiliki landasan teologis yang kuat dan menjadi sarana utama bagi pembentukan iman yang dewasa dalam kehidupan jemaat. Praktik disiplin rohani yang konsisten, seperti doa, pembacaan Firman, dan persekutuan terbukti memiliki keterlibatan jemaat dalam pelayanan serta menumbuhkan karakter Kristus yang nyata dalam kehidupan sehari-hari. Dengan demikian, disiplin rohani tidak hanya memperkuat pertumbuhan iman individu, tetapi juga memberikan implikasi signifikan terhadap kemajuan dan pertumbuhan gereja lokal secara holistik